Breaking Into Language in a New Modality: The Role of Input and Individual Differences in Recognising Signs - Hofweber, Julia Elisabeth; Aumonier, Lizzy; Janke, Vikki; Gullberg, Marianne; Marshall, Chloe (Frontiers in Psychology, 2022)
A key challenge when learning language in naturalistic circumstances is to extract linguistic information from a continuous stream of speech. This study investigates the predictors of such implicit learning amongst adults exposed to a new language in a new modality (a sign language). Sign-naïve participants (N=93; British-English speakers) were shown a 4-minute weather forecast in Swedish Sign Language. Subsequently, we tested their ability to recognise 22 target sign forms that had been viewed in the forecast, amongst 44 distractor signs that had not been viewed. The target items differed in their occurrence frequency in the forecast, and in their degree of iconicity. The results revealed that both frequency and iconicity facilitated recognition of target signs cumulatively. The adult mechanism for language learning thus operates similarly on sign and spoken languages as regards frequency, but also exploits modality-salient properties, e.g., iconicity for sign languages. Individual differences in cognitive skills and language-learning background did not predict recognition. The properties of the input thus influenced adults’ language learning abilities at first exposure more than individual differences.